Artificial intelligence-enabled digital transformation in elderly healthcare field: Scoping review. (January 2023) - Lee, Ching-Hung; Wang, Chang; Fan, Xiaojing; Li, Fan; Chen, Chun-Hsien
Abstract: As the ageing population grows continuously, traditional healthcare providers are experiencing difficulty in keeping up with changing and unpredictable demands as well as rising customer expectations. Artificial intelligence (AI) technology is quickly becoming a potent instrument for accelerating the digital transformation in the aged healthcare sector to deal with the high cost, dynamic nature, and unpredictability of the user environment. In this study, we used a thorough literature analysis to examine the advancements brought about by AI in the field of healthcare for the elderly. The study analyzed AI-enabled elderly healthcare-related articles that were published between 2000 and 2021. In total, 63 articles were extracted from the Web of Science. The review revealed that several elderly healthcare fields have developed and implemented AI-enabled systems and scenarios. It also revealed that AI technology has a substantial positive impact on the elderly healthcare field and leads to significant improvements in this field. The foundation for upcoming studies in the area of aged healthcare is laid forth by this literature review. The findings provide practitioners with crucial references for using artificial intelligence technology in elderly healthcare as well as suggestions for future research topics.